The Effectiveness of Cognitive-Emotional-Social Working Memory Training on Improving Verbal Creativity and Academic Self-Efficacy of Elementary School Students - Chari, Mohammad Ali; Salimi, Samaneh; Alisofi, Allah nazar (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The aim of the present study was to investigate the effectiveness of cognitive-emotional-social working memory training on improving verbal creativity and academic self-efficacy among elementary school students. Methods and Materials: The research method was quasi-experimental, utilizing a pretest-posttest design with a control group. The statistical population included all fifth-grade students in the city of Zabol during the 2022-2023 academic year. The study sample consisted of 40 students with poor working memory performance, selected through multistage cluster random sampling, and randomly assigned to experimental and control groups (20 students in each group). To collect data, the Torrance Test of Verbal Creativity (1979) and the Academic Self-Efficacy Scale by Jing and Morgan (1999) were used. In the pretest phase, both groups were assessed using these instruments. The experimental group received working memory training over three months, consisting of 20 sessions, each lasting 90 minutes, while the control group did not receive any intervention. Data were analyzed using analysis of covariance. Findings: The results showed that cognitive-emotional-social working memory training significantly improved verbal creativity and academic self-efficacy among students. Conclusion: Based on the findings of this study, it appears that cognitive-emotional-social working memory training, due to its multi-faceted, diverse, numerous, and ability-appropriate tasks, is effective in enhancing verbal creativity and academic self-efficacy in students with poor working memory performance.